MicroRNA signature in patients with eosinophilic esophagitis, reversibility with glucocorticoids, and assessment as disease biomarkers - Lu, Thomas X.; Sherrill, Joseph D.; Wen, Ting; Plassard, Andrew J.; Besse, John A.; Abonia, Juan Pablo; Franciosi, James P.; Putnam, Philip E.; Eby, Michael; Martin, Lisa J.; Aronow, Bruce J.; Rothenberg, Marc E. (Journal of allergy and clinical immunology, 2012)
The role of microRNAs (miRNAs), a key class of regulators of mRNA expression and translation, in patients with eosinophilic esophagitis (EoE) has not been explored. We aimed to identify miRNAs dysregulated in patients with EoE and assess the potential of these miRNAs as disease biomarkers. Esophageal miRNA expression was profiled in patients with active EoE and those with glucocorticoid-induced disease remission. Expression profiles were compared with those of healthy control subjects and patients with chronic (noneosinophilic) esophagitis. Expression levels of the top differentially expressed miRNAs from the plasma of patients with active EoE and patients with EoE remission were compared with those of healthy control subjects. EoE was associated with 32 differentially regulated miRNAs and was distinguished from noneosinophilic forms of esophagitis. The expression levels of the most upregulated miRNAs (miR-21 and miR-223) and the most downregulated miRNA (miR-375) strongly correlated with esophageal eosinophil levels. Bioinformatic analysis predicted interplay of miR-21 and miR-223 with key roles in the polarization of adaptive immunity and regulation of eosinophilia, and indeed, these miRNAs correlated with key elements of the EoE transcriptome. The differentially expressed miRNAs were largely reversible in patients who responded to glucocorticoid treatment. EoE remission induced a single miRNA (miR-675) likely to be involved in DNA methylation. Plasma analysis of the most upregulated esophageal miRNAs identified miR-146a, miR-146b, and miR-223 as the most differentially expressed miRNAs in the plasma. We have identified a marked dysregulated expression of a select group of miRNAs in patients with EoE and defined their reversibility with glucocorticoid treatment and their potential value as invasive and noninvasive biomarkers.